上唇に発生した多形腺腫由来癌の1例 - 濱田, 良樹; 新井, 剛; 馬杉, 亮彦; 長谷部, 充彦; 重松, 宏昭; 宮田, 幸長 (日本口腔外科学会雑誌, 2022)
Carcinoma ex pleomorphic adenoma is a rare malignant salivary gland tumor. It occurs more commonly in the parotid gland and rarely develops in the upper lip. We report a case of carcinoma ex pleomorphic adenoma arising in the left upper lip in a 63-year-old woman. The patient visited our hospital with the chief complaint of left upper lip swelling, which had been present for 10 years. In the clinical examination, an elastic-hard, painless, movable 25 × 15 mm mass was palpated in the left upper lip. MRI revealed a mass lesion with well-defined borders in the left upper lip area. T1-weighted images indicated moderate intensity, whereas fat-suppressed T2-weighted images showed high intensity. An incisional biopsy was performed under local anesthesia, and the initial histopathological diagnosis was pleomorphic adenoma. The tumor was subsequently removed under general anesthesia. Histological examination of the resected specimen led to a diagnosis of noninvasive carcinoma ex pleomorphic adenoma with a malignant component of salivary duct carcinoma. No sign of recurrence or metastasis has been observed in the two years and two months after surgery.